Answer: 60
Step-by-step explanation:
Let's solve the equation:
9x+27 = 9(x+2)+9 ← Distribute 9 to the x and 2
9x+27 = 9x+18+9 ← Combine like terms
9x+27 = 9x + 27 ← Subtract 27 from both sides
9x = 9x
Infinitely many solutions would be correct because no matter what x is, it will always equal each other the both sides of the equation because it is 9 times x on both sides.
Answer:
Your answer is 116
Hope that this is helpful. Tap the crown button, Mark my answer as............. BRAINLIST......... Like & Follow me to get more answer.
Answer:
x=3
Step-by-step explanation:
Right triangle so you can use pythagorean theorem
a squared + b squared = c squared
b=x
14^2 + b^2= 17^2
14+b=17
b=3
The situations can be represented by the exponential function f(x)=60x1.15^x
After 7.86 years the value of the investment will be three times the initial value (If you round to the nearest dollar)
After 8 years the value of the investment will be $184.00 (If you round to the nearest dollar)